ILLUSTRATION OF BRAILLE BOOKS IN LITHUANIA (BEFORE 1963): LINKS WITH THE EUROPEAN PRACTICE - RAUDONIENĖ, DIANA (Knygotyra, 2011)
The subject of the article is the history of publishing Braille books with raised-line illustrations for blind readers in Lithuania. The vast majority of illustrated Braille books were published by the Publishing House of the Lithuanian Society of the Blind during the period 1963–1989. Professional Lithuanian artists, among them well-known graphic artists and illustrators, were commissioned to create raised-line illustrations for the Braille books. A completely unknown area was waiting for illustrators. Their task was to find new methods of conveying information so far considered to be accessible only to the sighted.The first book with rise-line illustrations for Lithuanian blind readers was published in 1958, five years before the Publishing House of the Lithuanian Society of the Blind was established. The illustrated Braille primer as well as a few other illustrated textbooks were published by the State Publishing House of pedagogical literature. Members of the Editorial Board for Textbooks for the Blind, whose responsibility in this publishing house was to prepare Braille books for printing, visited the Riga State Publishing House in Latvia in order to get acquainted with methods of printing illustrated books for blind readers. Latvians already had a five-year experience in publishing illustrated Braille books, since they started this work in 1953. So, Lithuanian illustrators were not the first to “invent” raised-line illustrations. Beside such quite a direct connection, there existed also not so evident or distinct links with the experience of other European countries in this area. Teachers who had worked in the Kaunas Institution for the Blind and the Vilnius School for the Blind in 1928–1940 were in touch with the up-to-date European educational practice, so the idea of using graphical material as teaching resources for blind students was not new at all in Lithuania. Relief maps as well as other educational material were used at the Kaunas Institution and Vilnius school. Thus, there was a certain context for publishing illustrated books for the blind at the time when the Publishing House of the Lithuanian Society of the Blind started doing this. Whether professional Lithuanian artists commissioned to create raised-line illustrations took this European experience into consideration is another question which is not discussed here. The aim of this study was to ascertain what was the context for publishing illustrated books for the blind in Lithuania at the beginning of the 1960s. This context is explored taking into account two main aspects: (1) history of organized education of the blind in Europe and in Lithuania, emphasizing the practice of creating and using raised-line graphical material for teaching purposes, and (2) the history of publishing illustrated books for the blind in Europe.
Keywords: ...